Заражение: [фантастический роман] / Сергей Тармашев ; художник Николай Ковалев - Тармашев Сергей Сергеевич (Ареал, 2011)
Экземпляры: АБ (20210329) / Инвентарный номер: 65616 / Цена: 150.00 / Сис.шифр: 84(2=411.2)6 / Авт.знак: Т 19 / ББК: 84(2=411.2)6